Diagnostic criteria for asthenic accommodative asthenopia in patients with computer vision syndrome - I.G. Ovechkin; I.S. Gadzhiev; Kozhukhov A.A; E.I. Belikova (РМЖ "Клиническая офтальмология")
I.G. Ovechkin1, I.S. Gadzhiev2, A.A. Kozhukhov1, E.I. Belikova1 1Academy of Postgraduate Education of the Federal Scientific and Clinical Center  of the Federal Medical Biological Agency of Russian Federation, Moscow, Russian Federation 2Stavropol State Medical University, Stavropol, Russian Federation Aim: to assess the prevalence and clinical functional features of asthenic accommodative asthenopia in patients with computer vision syndrome. Patients and Methods: 86 men (172 eyes) aged 24–36 years (mean age 28.6±1.4 years) were examined. Major inclusion criteria were occupational daily activities (at least 2 years) regarded as a visually intensive work related to electronic chart displays (at least 8 hours daily) with a high level of responsibility for a final result; complaints which are typical of accommodative asthenopia and evident of its subcompensation or decompensation; low myopia (SE <3.0 diopters) or emmetropia; no ocular disorders (excepting refractive errors). Results: the analysis of basic diagnostic criteria demonstrated that habitually excessive accommodation strain (HEAS) was diagnosed in 51 patients (59.3%) and asthenic accommodative asthenopia in 19 patients (22.1%). In 16 patients (18.6%), the parameters did not meet the criteria of the investigated types of asthenopia. The most typical accommodative disorders in asthenic accommodative asthenopia are the significant reduction of accomodogram growth parameters and the high-frequency component of accommodative microfluctuations. The reasons for these phenomena are asthenization and weak ciliary muscle. Additionally, patients with asthenic accommodative asthenopia were characterized by the lowest score of the quality of visual life and subjective psychophysiological status compared to HEAS patients and controls. Conclusion: asthenic accommodative asthenopia is characterized by specific clinical functional and diagnostic criteria identified by both conventional and modern methods of the examination of visual accommodative system. These criteria can be recommended to assess the efficacy of preventive and therapeutic measures. Keywords: asthenopia, computer vision syndrome, accommodation, objective accommodography. For citation: Ovechkin I.G., Gadzhiev I.S., Kozhukhov A.A., Belikova E.I. Diagnostic criteria for asthenic accommodative asthenopia in patients with computer vision syndrome. Russian Journal of Clinical Ophthalmology. 2020;20(4):169–174. DOI: 10.32364/2311-7729-2020-20-4-169-174.